K.H. Tubagus Ahmad Bakri Sempur’s Theological Thinking and Its Implications in Mashlahah Al-Islamiyyah Fi Ihkami Al-Tawhidiyyah - Kosasih, Ade; Mahdi, Sutiono; Fahrullah, Tb. Ace (International Journal Labs, 2022)
K.H. Tubagus Ahmad Bakri (died 1975) was a cleric in Sempur Village, Plered District, Purwakarta Regency, West Java. One form of his legacy is in the form of written works known as